RUMUSAN VISI MISI DAN KONSISTENSINYA TERHADAP KULTUR SEKOLAH - DINI DWI YUSTIA PUTERI; PRIHANTINI (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
This research is motivated by the implementation of the vision and mission of the school is less a reflection of the in shaping the culture of a good school, to the achievement of the goals of the school effectively. The purpose of this study was to determine the formulation of the vision and mission of the school is reflected in the culture of the school. The method used is qualitative research with descriptive approach exploratory. Population in this research is primary School Cluster Pasirjambu, Ciwidey, Bandung. Sampling technique in this research is purposive. The instrument used was a questionnaire, interviews, observation and analysis of documentation. Conclusion the results of the research are (1) Formulation of vision and mission that owned the school made with the editor that is clear, interesting, adapted to the conditions of the school, describe the expectations/ ideals of the school, and contains the results of the expected performance. (2) Criteria for the formulation of the vision and mission have not all met by the school, because has not contain instructions about the target service vision, mission and haven't made the acronym a vision that is meaningful. (3) The Procedures for the formulation of the vision and mission has not been pursued comprehensively by the school. (4) The Culture of the school is not consistent with the vision and mission set by the school. From the above findings, the results of ths study have implications for schools to carry out the vision and mission accordingly the formulation procedure has an academic code of ethics code and has a motto/slogan as if it can encourage the school culture in accordance with the relevance and material of the study of the vision and formulating concept of the school and school culture.